Incidence of snakebites in the area between Mbandaka and Motongambale in the commune of Mbandaka (Equateur Province), Democratic Republic of the Congo - Blaise Mokekola Engomba; Jean-Pau; Assumani Zabo Idrissa; Guy Ilumbe Bayeli; Aristarque Bulambo Mulonda; Monizi Mawunu; Engomba Mboyo Gires (Orapuh, Inc., 2024)
Introduction The study attempted to elucidate the problem of the management of snakebites and envenomations in rural areas. Purpose It aimed to assess the management of snakebite cases in the liquid space around the town of Mbandaka in the Equateur Province of the Democratic Republic of the Congo. Methods The area investigated started from the Moyotu-Iyale villages along the Ruki River, moving on to the Isiya-Limbila villages along the Congo River, and ending in the Bondo-Ngolo-Motongambale villages on the Likelemba River. The survey was conducted during the period January 2019 to December 2020. In addition to doctors in the Mbandaka Health Zone, herbalists, traditional practitioners, households with bite cases, and land chiefs were contacted. The survey required the administration of a questionnaire to those involved in the survey. Results According to gender, the percentage of healed persons is 89.23% for men and 89.98% for women. More people with after-effects (6.15%) were recorded among men than among women (4.66%). There were slightly more deaths among women (5.53%) than among men (4.62%). In modern medicine in private health facilities, 57 cases of bites were recorded during the study period. Six of these cases were declared cured (10.53%). 10 cases concerned subjects who had escaped with sequelae, i.e., 17.54%. The low score recorded in the latter cases is justified by the lack of an appropriate protocol for specific cases diagnosed based on modern equipment. Conclusion The pathology of snakebite and envenomation is a case of neglected pathology in the province of Equateur, but also, traditional medicine can treat the pathology given the percentage of cures achieved by traditional healers